Mosque As the Center of Economic Empowerment of the Millennial Generation in Garut Regency - Syaripudin, Enceng Iip; Raito, Raito; Aliyah, Siti; Gaussian, Gini; Sunarsa, Sasa (Indonesian Journal of Islamic Economics and Finance, 2023)
Mosques are the most important facilities for Muslims. There needs to be efforts by mosque administrators to make mosques the center of Muslim civilization, especially in efforts to empower the millennial generation. This research aims to analyze the role of mosques as centers for economic empowerment for the millennial generation in Garut Regency. The research method used is qualitative with a case study approach. Data collection was carried out through in-depth interviews, observation and documentation. The research results show that mosques have a strategic role in empowering the economy of the millennial generation in Garut Regency. Some of the roles of mosques include (1) Mosques as centers for creative economic activities, such as entrepreneurship training, business incubation, and promotion of MSME products; (2) Mosques as a place to distribute zakat, infaq and alms (ZIS) funds for the economic empowerment of the millennial generation; (3) Mosques as a space for collaboration and synergy between the millennial generation, mosque administrators and other stakeholders in developing economic empowerment programs; and (4) Mosques as centers for strengthening Islamic character and values ​​that support the economic development of the millennial generation.